2014
DOI: 10.1017/s0950268814003008
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the problem of blood culture contamination in the intensive care unit using an educational intervention

Abstract: Blood culture contamination (BCC) has been associated with unnecessary antibiotic use, additional laboratory tests and increased length of hospital stay thus incurring significant extra hospital costs. We set out to assess the impact of a staff educational intervention programme on decreasing intensive care unit (ICU) BCC rates to <3% (American Society for Microbiology standard). BCC rates during the pre-intervention period (January 2006-May 2011) were compared with the intervention period (June 2011-December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
(42 reference statements)
0
9
0
2
Order By: Relevance
“…Despite the strict aseptic procedures in VUmc, contamination rate is comparable to that of other similar sized European hospitals, where rates could be as high as 7.4% [26]. Some improvements could be achieved by implementing an educational program for nurses or by deploying a specialized phlebotomy team [7, 27, 28]. These educational programs should also include instructions regarding the amount of blood volume that should be collected, as underfilling of these bottles reduces sensitivity and increases contamination rate [29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strict aseptic procedures in VUmc, contamination rate is comparable to that of other similar sized European hospitals, where rates could be as high as 7.4% [26]. Some improvements could be achieved by implementing an educational program for nurses or by deploying a specialized phlebotomy team [7, 27, 28]. These educational programs should also include instructions regarding the amount of blood volume that should be collected, as underfilling of these bottles reduces sensitivity and increases contamination rate [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, those authors began with percentages that were lower than the ones in our units of study. Most research that carried out educational interventions of this sort reported a 3% to 4% reduction in contamination levels (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…In the paediatric population, Hall et al [11] showed a reduction in contamination rates by using sterile gloves and a sterile field for blood culture collection in the setting of a paediatric emergency department. Other studies have improved contamination rates by using different skin cleansing solutions [11,12], dedicated phlebotomy teams [13], commercially produced blood culture collection packs [14], staff education programs [15], and by improvements in hand hygiene [16]. Despite these measures, CoNS-positive blood cultures remain problematic for the physician and infant.…”
Section: Background and Aimmentioning
confidence: 99%